2021
DOI: 10.3390/ph14070683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Anti-Cellulite Herbal Emgel: A Randomized Clinical Trial

Abstract: Cellulite describes unsightly skin overlying subcutaneous fat around thighs and buttocks of post-pubescent females. A herbal ‘emgel’ containing volatile oils and extracts of A traditional Thai herbal compress was tested in a double-blind, placebo-controlled trial with 18 women aged 20–50 year with severe cellulite. Appearance of cellulite (primary outcome), thigh circumferences, skin firmness, and cutaneous blood flow (secondary outcomes) were assessed at baseline, 2, 4, 8 and 12 weeks with a 2-week follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Placebo-controlled, randomized studies have shown notable enhancements in cellulite severity with topical preparations containing caffeine and/or retinol [18]. Herbal Emgel, a compress that encapsulates 100-200 g of mixed herbs, was shown to be effective in reducing the severity of cellulite in 21 premenopausal women [19]. However, these studies were limited in size and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Placebo-controlled, randomized studies have shown notable enhancements in cellulite severity with topical preparations containing caffeine and/or retinol [18]. Herbal Emgel, a compress that encapsulates 100-200 g of mixed herbs, was shown to be effective in reducing the severity of cellulite in 21 premenopausal women [19]. However, these studies were limited in size and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the more convenient dosage form, anti-cellulite emgel, was freshly prepared and clinically tested. Its effectiveness was already proved and reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%